MG-116 Report of 2 families with emberger syndrome (GATA2 mutation): Recognition of variance in clinical phenotype allows detection prior to malignant presentation. (4th December 2015) - Niederhoffer, Karen Y; Dix, David; Rehmus, Wingfield; McGillivray, Barbara; Armstrong, Linlea
Abstract : Background: Emberger syndrome is caused by mutation in GATA2 and predisposes to myelodysplastic syndrome (MDS)/acute myelogenous leukaemia (AML), lymphedema, warts, subtle dysmorphic features, and, rarely, congenital anomalies. Objectives: To describe the heterogeneity associated with GATA2 mutation and highlight features that should prompt testing. Design/methods: Case report of 2 families with mutation-confirmed Emberger syndrome. Results: Family 1: The proband presented with warts and mouth ulcers. WHIM syndrome was considered when neutropenia and B-cell deficiency developed, despite negative CXCR4 testing. Years later, the patient developed AML with monosomy 7 and underwent chemotherapy and stem cell transplantation. Idiopathic leg lymphedema occurred. Family history was significant for warts. Re-examination identified subtle dysmorphisms. GATA2 sequencing detected a missense mutation. Family 2: Sibling 1 had a history of warts, mouth ulcers, ectopic anus, mild sensorineural hearing loss, and new-onset neutropenia. Bone marrow testing diagnosed MDS with monosomy 7. Sibling 2 had hypocellular, mildly dysplastic bone marrow. History included warts and leg lymphedema. Sibling 3 had mild bone marrow hypocellularity. Family history was significant for a parent with childhood warts and mouth ulcers. Siblings 1–3 had subtle dysmorphisms. GATA2 sequencing identified a nonsense mutation. Sibling 1 underwent stem cell transplantation. Siblings 2–3 are closely monitored. Conclusions: The literature is biassed towards individuals who present with overt haematological malignancies;however, Emberger syndrome can be recognised earlier. Suspicion should be high in individuals with persistent hematologic/immunologic abnormalities, warts refractory to treatment, and/or lymphedema particularly in the setting of subtle, but typical, dysmorphisms. Intervention before development of AML decreases morbidity/mortality.